Discourse Analysis of Thematic Structure: SEVENTEEN JOSHUA’s Speech in UNESCO Youth Forum - Kaonedy, Jesselyn; Nasution, Diantry Binarwaty Habibie; Istiqomah , Istiqomah; Sastia, May; Zein, T. Thyrhaya (Universitas Negeri Medan, 2025)
This study aimed to find the underlying messages in SEVENTEEN Joshua’s Speech in UNESCO Youth Forum through a textual metafunction analysis on the thematic structure. SEVENTEEN, a global K-Pop boy band, was chosen to deliver a speech as the representation of youth in UNESCO Youth Forum in Paris last 2023. This research used a descriptive-qualitative method, Halliday’s textual metafunction and Leech’s thematic meaning theories. Based on the findings, JOSHUA, the American member of SEVENTEEN, used a lot of unmarked themes in highlighting the group’s effort and dedication in promoting education. Meanwhile, most of the marked themes were used to highlight their long-lasting and consistent contribution to UNESCO. Therefore, this research concluded that JOSHUA made SEVENTEEN as the ‘main character’ in his speech.